Fostering Moral and Cultural Values through School-Based Practices: A Qualitative Study of Character Education - Putri, Dya Ayu Agustiana; Sari, Eka Yuliana (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2025)
Character education plays a crucial role in shaping moral, adaptive, and competitive generations in an era of globalization. In Indonesia’s multicultural context, strengthening culture-based character education is essential to instill moral and social values from an early age. This study aims to describe the implementation of culturally oriented character education at Muhammadiyah Elementary School, Sapen, Yogyakarta, and to analyze how such practices contribute to the formation of students’ personal and moral excellence. This study employed a descriptive qualitative approach involving participatory observations, in-depth interviews with teachers, students, and parents, as well as document analysis. Data were thematically analyzed through reduction, categorization, and interpretation stages to identify value patterns, behavioral expressions, and strategies for implementing culture-based character education. Findings reveal that core character values, discipline, honesty, responsibility, empathy, and religiosity, are consistently integrated into daily school life through morning tadarus activities, honesty canteens, traditional music (karawitan) lessons, and teacher modeling. These practices align with the dimensions of the Pancasila Student Profile and are supported by a human resource management system emphasizing integrity, commitment, and moral leadership. The integration of cultural and religious values within character education effectively fosters students’ holistic development, rooted in local wisdom yet responsive to global challenges. This study contributes a conceptual model of culture-based character education that can be replicated in other elementary schools and enriches the international discourse on value-based education in multicultural societies.